Prefrontal Cortex and Supplementary Motor Area Activation During Robot-Assisted Weight-Supported Over-Ground Walking in Young Neurological Patients: A Pilot fNIRS Study - van Hedel, Hubertus J. A.; Bulloni, Agata; Gut, Anja (Frontiers in Rehabilitation Sciences, 2021)
Introduction Rehabilitation therapy devices are designed for practicing intensively task-specific exercises inducing long-term neuroplastic changes underlying improved functional outcome. The Andago enables over-ground walking with bodyweight support requiring relatively high cognitive demands. In this study, we investigated whether we could identify children and adolescents with neurological gait impairments who show increased hemodynamic responses of the supplementary motor area (SMA) or prefrontal cortex (PFC) measured with functional near-infrared spectroscopy (fNIRS) when walking in Andago compared to walking on a treadmill. We further assessed the practicability and acceptability of fNIRS. Methods Thirteen participants (two girls, eleven boys, age 8.0-15.7 years) with neurological impairments walked in the Andago and on a treadmill under comparable conditions. We measured hemodynamic responses over SMA and PFC during ten walks (each lasting 20s.) per condition and analyzed the data according to the latest recommendations. In addition, we listed technical issues, stopped the time needed to don fNIRS, and used a questionnaire to assess acceptability. Results Hemodynamic responses varied largely between participants. Participants with a typical hemodynamic response (i.e., increased oxygenated hemoglobin concentration) showed large cortical activations during walking in Andago compared to treadmill walking (large effect sizes, i.e., for SMA: r = 0.91, n=4; for PFC: r = 0.62, n=3). Other participants showed atypical (SMA: n=2; PFC: n=4) or inconclusive hemodynamic responses (SMA: n=5; PFC: n=4). The median time for donning fNIRS was 28 minutes. The questionnaire indicated high acceptance of fNIRS, despite that single participants reported painful sensations. Discussion Repetitive increased activation of cortical areas like the SMA and PFC might result in long-term neuroplastic changes underlying improved functional outcome. This cross-sectional pilot study provides first numbers on hemodynamic responses in SMA and PFC during walking in Andago in children with neurological impairments, reveals that only a small proportion of the participants shows typical hemodynamic responses, and reports that fNIRS requires considerable time for donning. This information is needed when designing future longitudinal studies to investigate whether increased brain activation of SMA and PFC during walking in Andago could serve as a biomarker to identify potential therapy responders among children and adolescents undergoing neurorehabilitation.